The Analysis of English Course Book for Tenth Grade of Senior High School Based on Merdeka Curriculum - Wahyudin, Wahyudin; Novari, Ari Fajria; Rohimajaya, Nur Azmi (2025)
The research aims to analyze English textbooks Work in Progress. Based on the Independent Curriculum, there are many references for achievements learning that refers to six elements of English skills, namely listening, speaking, reading, viewing, writing and presenting in an integrated manner. The data analysis in this research was carried out by selecting data and presenting it isdata, interpret data, and draw conclusions. Data is evaluated with using the categories high, low, and null. Analysis is carried out based on chapters where this textbook has six chapters. Results of this research shows that in general the English book "Work in Progress" exists some elements of the English language that correspond to what is suggested by Merdeka curriculum which refers to six skills in English. For the listening element in textbooks in each chapter have a high level of Conformity with the curriculum merdeka, for the speaking element in the textbook Curriculum.There are only 5 chapters that have a high level of suitability, in the reading element in each the chapters have a low level of conformity with the independent curriculum, and the viewing elements in each chapter have a level high suitability because it is in accordance with the Merdeka curriculum.The Research and presenting elements in each chapter have levels high conformity refer in the grid of the book Work in Progress it can be concluded that based on that the English textbook "Work in Progress" is appropriate suggested by Merdeka curriculum even though there are elements that are still not appropriate.